Mechanisms of executive control: behavioral investigations of the conflict adaptation effect - Bugg, Julie M., author; DeLosh, Edward L., advisor; Clegg, Benjamin, committee member; Gingerich, Karla J., committee member; Davies, Patricia L., committee member (Colorado State University. Libraries, 2006)
The conflict adaptation effect refers to a reduction in reaction time on an incompatible trial of the Eriksen Flanker task that is preceded by another incompatible trial as compared to being preceded by a compatible trial. The repetition priming account contends that the effect is a memory phenomenon limited to complete repetition trials. The conflict monitoring account contends that preceding trial conflict triggers a tightening of control, making participants less susceptible to conflict on the subsequent incompatible trial. The effect is expected, therefore, on complete repetition and non-repetition trials. Experiments 1, 2, and 3 were designed to contrast the two accounts by manipulating the degree of conflict present on incompatible trials. In Experiment 1, conflict was manipulated by varying the frequency of incompatible trials. The conflict adaptation effect was found on repetition but not non-repetition trials, with a trend toward greater conflict adaptation in response to greater conflict in the mostly compatible condition. In Experiment 2, conflict was manipulated by varying the identity of the flanker stimuli, with left or right flankers expected to produce a greater degree of response conflict than up or down flankers. The conflict adaptation effect was observed for both repetition and non-repetition trials though a greater degree of conflict did not result in greater adaptation. In Experiment 3, conflict was manipulated by altering the size of the incompatible flankers to be either larger or smaller than the central stimulus. Again, the conflict adaptation effect was limited to repetition trials and the degree of conflict did not alter the magnitude of the effect. A negative priming explanation of the lack of conflict adaptation on non-repetition trials was not supported in Experiment 4, though a follow-up experiment revealed a 16 ms negative priming effect. Taken together, the results suggest that the conflict adaptation effect reflects repetition priming and under some conditions, conflict monitoring. Further clarifying the nature of these conditions such as the size of the response set, size of the stimulus set, and the length of the response to stimulus interval is an important next step in this line of research.
Keywords: cognitive therapy; cognitive psychology